State defending and neo-colonialism - Hotma Ivan Sirait; Sutrimo Sumarlan; Afrizal Hendra (Strategi Perang Semesta, 2022)
The development of an increasingly modern human mindset cannot eliminate the nature of domination that tends to be put forward. The provisions made are always followed by loopholes that become a way to satisfy the desire for domination. Neo-colonialism is a picture of human love for colonialism and a reminder that colonialism still exists and covered in other motivations at first. These are the reasons for this research. Totality is a comprehensive concept of togetherness to face the threat of neo-colonialism. The nature of totality becomes stronger if it is done with sincerity based on an understanding of love to the nation. Defense the country with efforts of Bela Negara (state defending), illustrate that "nation's soul" strengthening is the main element, which aims to detect and be able to overcome the threat of new colonialism. Research purpose was to analyze the efforts of state defending to face neo-colonialism, using descriptive analytic methods. The conclusion is that neo-colonialism entered in disguise and the implementation of state defending was a powerful way to counteract it. State defending must be introduced early on, through family and the surrounding environment sustainably. Including the development of state defending organization, is needed to expand coordination, interaction and monitoring.